Plan de manejo de los manglares del estero Guajabal en el archipiélago de Jambelí - Márquez Bustamante, César Atilio (2014)
The Association of Fish Production and Allied Craft "San Antonio" is a group formed by traditional users of the goods and services of the mangrove ecosystem. Are domiciled in Puerto Bolívar Parish in Canton Machala, El Oro Province Legal status being requested will be granted by Ministerial Agreement. They do their work in the area of Bajo Alto, Temples, Loma Loma Grande and Chica, on the coast of the province of El Oro Aware that need sustainably manage mangrove resources (eg, shells, crabs and fish) to ensure source of employment and livelihood, have decided to apply the Agreement sustainable Use and Custody of 631.4 hectares of mangroves. The area is characterized by a tropical climate megathermic Seco, which is characterized by annual rainfall is between 500 and 1000 mm, distributed between January and April, and this very dry climate in summer and high temperatures in 7 of months (Gordillo, O. 2009). From an ecological perspective, the remaining vegetation, consisting of mangrove ecosystems, it becomes a very important component that determines the existence of biodiversity and habitat, wildlife refuge center and source of goods and services necessary to ensure the quality of life of people in their environment. The vegetation comprises mainly mangrove. Mangrove species present in the area include: red mangrove, Rhizophora mangle (Rhizophoraceae); colorado red mangrove, mangrove guan ((Rhizophoraceae), Rhizophora harrisonii, white mangrove, Laguncularia racemosa, and Black mangrove, black mangrove, Avicennia germinans (Avicenniaceae). The fauna is characteristic of the mangrove ecosystem, where species of birds like magnificens Frigate, Frigate minor, Phalacrocorax auritus, Pelecanus thagus, Ardea alba, Egretta caerulea dominated, among others. Benthic organisms also predominate as Ucides occidentalis, tuberculous Anadara, Anadara similis, Anadara grandis; and fish from Migilidae, Ariidae, Tetradontidae, Gerreidade, Haemulidae, Bothidade, Soleidade, Engraulidae and Clupeidae. The main management problems found were: i) exploitation of natural resources of the mangrove ecosystem; ii) environmental impacts for the misuse of environmental goods and services; and iii) low quality of life of members of the association. The management plan focused on three programs: i) use Plan, ii) Plan monitoring and surveillance; iii) Monitoring and Evaluation Plan. This document details the actions to be performed The Association of Fish Production and Allied Craft "San Antonio" for the integrated management and sustainable use of the area to guard applied to the Undersecretariat of Marine and Coastal Management under the Ministry of Environment.